Penerapan 3M (Mewarnai, Menggunting, dan Menempel) Terhadap Kemampuan Motorik Halus Anak Usia Dini RA Al- Muminun Lebak - Erma Noor Wahyuningsih; Indah Istikhomah; Bismi Nuraeni Putri; Enci Zarkasih; Elis Haerani (Institut Nalanda, 2025)
Child development is a process of change in which children learn to master higher levels of aspects of movement, thinking, feeling and interaction, both with others and with objects in their environment. 3M activities become an effective medium for children's fine motor skills because they can learn various values such as creativity, thoroughness, honesty, patience, harmony, and responsibility. This study aims to analyze the effectiveness of the application of 3M to fine motor skills in early childhood at RA Al-Muminun Wanasalam Lebak. This study uses a descriptive qualitative research approach. The main informants in this study were 2 teachers and 1 school principal as supporting informants at RA Al-Muminun Wanasalam Lebak. The results of the study show that the use of the 3M activity application method is proven effective in improving the fine motor skills of early childhood. However, the success of the 3M application depends heavily on several factors, such as the selection of colors, tools, and materials that are appropriate to the child's age and development, the ability of 3M activities during the activity, and the follow-up after the 3M activity. In addition, this study also highlights the importance of the role of parents in supporting children's fine motor skills at home.